(untitled) (American Journal of Energy and Natural Resources, 2025)
Solar Energy Essential in Global Drive for Net Zero Emissions This paper sets out to address the complex role of solar power as an enabler for decarbonization, highlighting both policy and technology-related matters. We assess the effectiveness of different policy instruments in fostering solar energy uptake: financial incentives and regulatory frameworks that level the playing field with other technologies or curtail them by limiting, e.g., fossil fuel use, carbon pricing mechanisms, and international cooperation. We also review key technological advancements in photovoltaics, energy storage, and grid integration that are essential for solar energy to play an optimized role in a sustainable energy future. For these intents and purposes, we explore how new technologies such as perovskite solar cells (PSCs), concentrated solar power (CSP), or building-integrated photovoltaics (BIPV) could offer a significant enhancement of efficiency and dynamism in converting sunlight into electricity. Case We explore the dos and don’ts of being a perfect project through stories from successful solar energy integration projects. We assess the challenges and opportunities associated with solar powering in the future, underscoring the provision of cohesive policy as well as technology road-maps to achieve global net-zero targets. Our study underscores the potential of solar energy as a transformative resource. It provides direction to policy-makers, scholars, and industry actors regarding pathways that may accelerate the deployment of this increasingly vital renewable technology.